Protein misfolding diseases methods and protocols - Gomes, Cláudio M. 1970- (Methods in Molecular Biology, 2019)
This detailed book gathers a broad collection of experimental approaches to assist researchers in setting up different methods to investigate protein conformational disorders. Beginning with a section on assays focusing on biophysical approaches to study protein (mis)folding, the volume continues with sections on cellular and proteostasis assays as well as assays for protein folding correction and recovery, combining methods such as thermal shift assays, in silico improvement of protein solubility, and compound screening, an important area of research as it may open avenues for therapeutic strategies. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips for troubleshooting and avoiding known pitfalls. Authoritative and practical, Protein Misfolding Diseases: Methods and Protocols serves as an ideal guide for researchers seeking to advance our knowledge of protein conformational disorders